Panel: Research Sponsors for Cybersecurity Research and the Human Factor. (November 2019) - Gutzwiller, Robert S.; Cosley, Dan; Ferguson-Walter, Kimberly; Fraze, Dustin; Rahmer, Robert
A panel of past or current sponsors of human-centered research in cybersecurity. Attendees from industry, government and academia alike who are interested in cybersecurity research will benefit from hearing these panelists describe their experience and their views on the state of the field, current knowledge gaps and future directions for winning proposals.